Patient and provider factors associated with follow-up for positive depression screens in adults: a retrospective review of University of Utah primary and specialty care clinics - Tess Battiola; Tanner Ellison; Danica Dummer; Rachel Weir; Katie Kaput; Deepika Reddy (BMJ Open)
Objective To identify patient and provider factors associated with lower rates of follow-up for positive depression screens in outpatient settings.Design Retrospective cohort study with electronic health record analysis investigating factors associated with follow-up care for patients with moderate-to-severe depressive symptoms. Patient and provider variables were associated with rates of follow-up for positive depression screens.Setting University of Utah and University of Utah Health-affiliated primary care and specialty clinics.Participants Adults who screened positive for depressive symptoms (score≥10) on the Patient Health Questionnaire (PHQ-9) at an ambulatory visit between 1 January 2021 and 31 January 2022. A total of 17 651 patients were included in the study.Outcome measures Follow-up for positive depression screens was defined as a new antidepressant prescription or completed mental health visit. Variables associated with follow-up included patient demographic data, anthropometric measures, geographical classification, primary language, comorbidities and socioeconomic factors as well as provider demographics, level of training and clinic type.Results 5396 patients (30.6%) did not receive follow-up care for a positive PHQ-9 screen. Factors associated with lower rates of follow-up included male patients (gender; p=0.013), older patients (age group; p=0.016), non-White patients (ethnicity; p<0.0001), non-English (primary language; p<0.0001), lack of insurance (p<0.0001), older providers (p=0.027), male providers (p=0.0037) and attending-level providers (p<0.0001).Conclusions Significant discrepancies in follow-up for positive depression screens in the ambulatory setting exist, particularly among racial/ethnic minority groups and patients who are non-native English speakers. Older providers and attending-level providers were less likely to facilitate follow-up for positive depression screens in their clinics.